Carbon Dioxide Reforming of Methane Over Bimetallic Co-X/Activated Carbon Catalysts (X = Ni, Cu, Fe, Mg, Ca) - Zhang, Guojie; Du, Yannian; Zhang, Yongfa (Asian Journal of Chemistry, 2014)
Carbon dioxide reforming of methane has been studied over Co/activated carbon catalysts promoted with different metal additives (Ni, Cu, Mg, Ca, Fe) aiming to improve the performance of the catalysts and increase their resistance to coking. It was found that the type of the promoter significantly affected the metal dispersion properties and catalytic performances of Co/activated carbon catalysts in the temperature range of 750-850 ºC. Nickel doped Co/activated carbon displayed the highest activity among all the catalyst. This is mainly result due to nickel-cobalt formation alloy.